Isotretinoin for the treatment of acne in pediatrics: what should pediatricians know? (Archives of Pediatrics of Uruguay, 2025)
Isotretinoin, or 13-cis-retinoic acid, is a retinoid derived from vitamin A widely used in the treatment of severe cases of acne and other dermatological conditions.This drug is distinguished by its ability to act on multiple pathophysiological aspects of acne, such as reducing the size and activity of the sebaceous glands, reducing colonization by Cutibacterium acnes and attenuating inflammation. These actions not only achieve significant acne control during treatment, but may also offer a sustained long-term effect due to structural remodeling of the sebaceous glands, which decreases recurrence.Acne is a disease that can leave physical and psychological scars, so early and effective treatment is essential to prevent these complications, improving the quality of life of these patients.Although the treatment of moderate-severe acne is usually conducted by a dermatologist, acne isotretinoina we believe it is important that pediatricians become familiar with this drug, its indications, the most frequent adverse effects, as well as the complications that may arise.
Keywords: Isotretinoin; Vulgar Acne; Pediatrics